2015
DOI: 10.1016/j.ejpb.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interaction of nanoparticles with mucin for drug delivery applications using dynamic light scattering

Abstract: Drug delivery via the eye, nose, gastrointestinal tract and lung are of great interest as they represent patient-compliant and facile methods to administer drugs. However, for a drug to reach the systemic circulation it must penetrate the "mucus barrier". An understanding of the characteristics of the mucus barrier is therefore important in the design of mucus penetrating drug delivery vehicles e.g. nanoparticles. Here, a range of nanoparticles -silica, aluminium coated silica, poly (lactic-co-glycolic acid) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 29 publications
6
39
0
Order By: Relevance
“…The combined particle size distribution for the various replicates shows no change in the position and intensity of the peak. In line with previous studies, (9) the apparent dimension of bare PLGA is significantly shifted to larger sizes upon addition of mucin, reflecting strong mucin/NP hydrophobic interactions, which likely provide a basis for mucoadhesive NPs ( Supplementary Fig. S1A; Supplementary Data are available online at www.liebertpub.com/jamp).…”
Section: Development Studies Of Dppc/plga Hnps For Sirna Loadingsupporting
confidence: 89%
See 2 more Smart Citations
“…The combined particle size distribution for the various replicates shows no change in the position and intensity of the peak. In line with previous studies, (9) the apparent dimension of bare PLGA is significantly shifted to larger sizes upon addition of mucin, reflecting strong mucin/NP hydrophobic interactions, which likely provide a basis for mucoadhesive NPs ( Supplementary Fig. S1A; Supplementary Data are available online at www.liebertpub.com/jamp).…”
Section: Development Studies Of Dppc/plga Hnps For Sirna Loadingsupporting
confidence: 89%
“…The interactions of hNPs with mucin were further investigated by DLS as previously reported. (9) Briefly, the hNP dispersions in mucin were examined with the Malvern Zetasizer Nano ZS (Malvern Instruments, United Kingdom). Experiments were run in triplicate and results are reported as representative size distribution by intensity of hNPs in mucin versus hNPs in water.…”
Section: Characterization Of Dppc/plga Hybrid Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a nanoparticle to traverse mucus, it must possess desired surface characteristics to avoid adhesion and steric inhibition by the mucin fiber mesh. It has been demonstrated that poly(lactic-co-glycolic acid) (PLGA) and polystyrene particles functionalized with mucus inert polymers such as poly(ethylene glycol) (PEG) enhanced mucus transport in pig gastric mucus (Dawson et al, 2004; Griffiths et al, 2015), pig intestinal mucus (Abdulkarim et al, 2015; Groo et al, 2014), mouse vaginal mucus (Ensign et al, 2012b), human cervicovaginal mucus (Lai et al, 2007; Mert et al, 2012; Tang et al, 2009a; Xu et al, 2013a; Xu et al, 2015), human respiratory mucus (Schuster et al, 2013), cystic fibrosis (CF) sputum (Suk et al, 2011; Suk et al, 2009; Tang et al, 2009a), and bovine vitreous ex vivo (Xu et al, 2013b). Moreover, our group has previously demonstrated that carboxyl and amine-functionalized nanoparticles disrupt the mucus barrier and improve drug permeation up to 4.9-fold with 200 nm carboxyl-nanoparticles in porcine gastric mucus compared controls without particles (McGill and Smyth, 2010).…”
Section: Transmucosal Drug Deliverymentioning
confidence: 99%
“…Isothermal titration calorimetry (ITC), a technique which measures the heat released or absorbed during a biomolecular binding event[88], revealed that binding of PLGA-PEG nanoparticles (~100 nm) with Sigma bovine submaxillary gland mucin decreased as a function of conjugated PEG concentration (0–25 wt% PEG). Dynamic light scattering was also used to determine interactions between Sigma gastric mucin and negatively- or positively-charged silica nanoparticles (10–15 nm diameter)[89]. Solutions containing nanoparticle only, mucin only, and nanoparticle mixed with mucin were analyzed at 37 °C with a scattering angle of 173 degrees.…”
Section: Isolated Mucus Modelsmentioning
confidence: 99%